MANAJEMEN STRATEGI PROMOSI PRODUK PEMBIAYAAN PERBANKAN SYARIAH - Frity Sundariani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Essentially, sharia banking is a banking system in which the business is governed by Islamic sharia, as outlined in the Al-Qur'an and Sunnah (Al-hadith). According to Bank Indonesia, there are two types of banks that provide financing: conventional banks and banks. Sharia. Muslims all over the world, including Muslims in Indonesia, have been affected by the interest system used in conventional banking. Premium in cash in fiqh is sorted as usury, which is something precluded by sharia (haram). Sharia Bank is one example of a financial institution that does not charge interest for this fundamental reason. Companies in the banking industry that operate in this era of globalization have been motivated to compete more effectively as a result of the demands placed on them by the banking industry